Studi Pertumbuhan Mikroskopis: Pengaruh Suhu dan Curah Hujan terhadap Aktivitas Kambium pada Kayu Jelutung : Studied of Microscopic Growth: the Influence of Temperature and Rainfall on Cambium Activities in Jelutong Wood - Lies Indrayanti; Sri Noegroho Marsoem (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
The cambium activity in wood formation is highly affected by temperature and rainfall. The aim of the present study was to investigate the cambium activities, i.e., cell number, cell proportion, and cell size during the growth period of jelutong wood. The pinning method was employed as the marking for initiating the observations on the formation and sizes of wood cells. The results revealed three patterns of the effect of the change in temperature and rainfall. First, when both temperature and rainfall increase, the number of fiber cells number increases, while the vessel cells, parenchyma cells, and rays decrease. The size of new fiber cells alters in which cell diameter, lumen diameter, and cell wall thickness increase, but fiber length decreases. This pattern forms short cells with thick cell walls. In the observation when temperature increases and rainfall decreases, the number of fiber cells and vessel cells increases while the number of parenchyma cells and rays decreases. New fiber cells have an increase in cell diameter, lumen diameter, and fiber length, but a decrease in cell wall thickness. The cells formed in the second pattern are long cells with thin cell walls. The third observation is when the temperature increases and rainfall decreases. In this pattern, the number of fiber cells, vessel cells, and cell size decrease, but the number of parenchyma cells and rays increases. This pattern forms short cells and thick cell walls. It causes variations in the properties of wood and affects the wood quality. Kata kunci (Keywords): cambium activity, temperature, rainfall, wood formation.